Optical and x-ray diagnostics of a plasma focus / Lee Ming Chuan - Lee , Ming Chuan (2017)
The plasma pinch evolution and X-ray emission of a dense plasma focus are investigated with several diagnostics techniques together with the time resolved and time integrated imaging techniques. The experiment is carried out on the 3.3 kJ Plasma Focus Facility, UNU/ICTP PFF (United Nations University/International Centre for Theoretical Physics Plasma Focus Facility) with neon gas filled at the pressure of 4 mbar. ICCD camera and MCP (microchannel plate) camera setups are established to capture the visible spectra and the X-ray emission from the plasma focus at radial direction aiming on the anode axis. Magnetic probe and an array of PIN diode detectors are used to measure the rate of change of the discharge current and time profile of the X-ray emissions. The time profile of the discharge current and discharge voltage signals are correlated to the timing of the ICCD imaging and MCP imaging. An X-ray spectrometer is employed to measure the integrated emission of the neon plasma. The current sheath dynamics in their radial trajectory and compression phase have been revealed by a series of images carefully obtained at different timings. The neon plasma focus is observed to have multiple compressions. The radial compression phase is explained by considering three main regions (first region, second region and third region). Neon X-ray emission is observed in the first region, while X-ray emission from copper K-alpha is measured in the second and third region. The electron temperature estimated based on the neon X-ray emission is around 500 eV and the highest electron temperature has been estimated at 10 keV.